Molecular identification of cultivable bacteria in the gut of adult Bactrocera tau (Walker) and their trapping effect. Issue 12 (14th August 2018) - Luo, Mijuan; Zhang, Hehe; Du, Yinggang; Idrees, Atif; He, Longyan; Chen, Jiahua; Ji, Qing′e
Abstract: BACKGROUND: It has been shown that some bacteria can attract their hosts. Our research aimed to identify cultivable bacterial isolates in the guts of sexually mature adult female and male Bactrocera tau and to evaluate their utility in trapping of B. tau . RESULTS: Forty‐one strains of bacteria were isolated and identified from B. tau with morphological, physiological, biochemical and 16S rDNA analysis. The dominant bacterial genera shared by both females and males were Enterobacter, Providencia and Serratia . Thirteen bacterial isolates selected from female and male B. tau adults were cultured, and the attractiveness of bacterial fermented liquid and autoclaved supernatants from these strains to B. tau adults was tested. The laboratory test showed that both the autoclaved supernatants and fermented liquid could attract male and female B. tau, and the former was substantially more effective, with the autoclaved supernatants from all strains being significantly more attractive to adult B. tau . BF16, BF(12), BF23 and BF(32) were the most attractive bacteria to 8‐day‐old and sexually mature B. tau . Furthermore, the results of a subsequent field cage test showed that BF(12), BF23, and BF(32) were significantly more attractive to B. tau adults. CONCLUSION: These results provide useful information for the development of bacterial biocontrol agents and their application as insecticides. © 2018 Society of Chemical Industry Abstract : We found that four bacterial strains were highly attractive to both male and female adults of B. tau . The identified bacterial strains may be useful in development of biocontrol agents.